Neurocommunicative methodologies: attention and emotion of the audiovisual story in the classroom - Vanessa Izquierdo; María Luisa Garrigues (Multidisciplinary Journal for Education, Social and Technological Sciences)
Audiovisual content as a learning tool has been incorporated extensively into lecture classes. Emotion-cognition is intrinsic to the functioning of the human brain, and therefore can explain the acquisition of knowledge and competencies in the educational field, and more specifically, the transformative impact on digital natives. Advances in the study of the brain have allowed for quantitative measurement of attentional (EDL) and emotional (EDR) terms. The objective of this article is to analyze and evaluate the correlation between attention and emotion during the viewing of two videos shown in a classroom in the academic space of a university. The method consisted of recording the electrodermal activity of various groups of Audiovisual Communication and Advertising and Public Relations students during the viewing of the two audiovisual stories. The main results and conclusions link characteristics of the audiovisual narrative and technical-expressive qualities and objectives of the videos with the levels of EDL and EDR recorded by the device and establish advanced lines of research in the field of neuroeducation and neurocommunication.